2017
DOI: 10.1177/1010428317718135
|View full text |Cite
|
Sign up to set email alerts
|

The long non-coding RNA MALAT1 promotes the migration and invasion of hepatocellular carcinoma by sponging miR-204 and releasing SIRT1

Abstract: Increasing evidence supports the significance of long non-coding RNA in cancer development. Several recent studies suggest the oncogenic activity of long non-coding RNA metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) in hepatocellular carcinoma. In this study, we explored the molecular mechanisms by which MALAT1 modulates hepatocellular carcinoma biological behaviors. We found that microRNA-204 was significantly downregulated in sh-MALAT1 HepG2 cell and 15 hepatocellular carcinoma tissues by qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
70
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 50 publications
2
70
0
Order By: Relevance
“…Therefore, the identification of key lncRNAs associated with HCC is critical to clarify this disease and identify novel therapeutic targets. It is reported that lncRNA GAS5 is downregulated in HCC, and its overexpression can impede cell migration and invasion ; the expression of lncRNA HOTAIR in HCC is elevated, and patients with high expression of it have a poor prognosis ; moreover, the expression of lncRNA MALAT1 is also confirmed to be an independent prognostic factor for HCC . It is worth noting that the expression of DUXAP8 is closely related to the occurrence and progression of a variety of tumors.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Therefore, the identification of key lncRNAs associated with HCC is critical to clarify this disease and identify novel therapeutic targets. It is reported that lncRNA GAS5 is downregulated in HCC, and its overexpression can impede cell migration and invasion ; the expression of lncRNA HOTAIR in HCC is elevated, and patients with high expression of it have a poor prognosis ; moreover, the expression of lncRNA MALAT1 is also confirmed to be an independent prognostic factor for HCC . It is worth noting that the expression of DUXAP8 is closely related to the occurrence and progression of a variety of tumors.…”
Section: Discussionmentioning
confidence: 95%
“…The pathogenesis is a complex process with multiple factors and steps. Growing studies have shown that lncRNAs are abnormally expressed in human tumors, including HCC . Therefore, the identification of key lncRNAs associated with HCC is critical to clarify this disease and identify novel therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long noncoding RNAs (LncRNAs) are noncoding RNAs longer than 200 nucleotides . Accumulating evidence showed lncRNAs, such as MALAT1, HOTAIR, and H19, are associated with tumor proliferation, survival, and metastasis . lncRNA KCNQ1OT1, located on chromosome 11p15.5, which has been demonstrated that play a vital modulator in proliferation and metastasis of various tumors, such as cholangiocarcinoma, hepatocellular carcinoma, and breast cancer .…”
Section: Introductionmentioning
confidence: 99%
“…6 MALAT1, H19, HULC, and HOTAIR have been found to act as oncogenes or tumor suppressors. [7][8][9] 2 | MATERIALS AND METHODS…”
mentioning
confidence: 99%